Socioeconomic Barriers to Rhegmatogenous Detachment Surgery in Brazil. (23rd November 2014) - Carricondo, Pedro Carlos; Tanaka, Tatiana; Shibata, Suellen Tiemi; Zacharias, Leandro Cabral; Leite, Thiago Aragão; Abalem, Maria Fernanda; Takahashi, Walter Y.
Abstract : Purpose . To verify access barriers patients with retinal detachment face to arrive at a reference center and to evaluate patients' knowledge about the disease. Methods . Transversal study that applied a questioner to 65 patients of the Clinical Hospital of the University of Sao Paulo with retinal detachment between February and August of 2010. Results . Reasons for not performing the surgery in other services were as follows: 47% were referred because there was not vitreoretinal surgeon at original service; 27% could not afford the surgery, had no health insurance, or had no coverage at health insurance plan for the procedure. Time between the first symptom and the arrival at our service was as follows: 18 patients arrived in up to 7 days; 35 between 8 and 30 days; 8 between 31 and 90 days; 5 in more than 90 days. Reasons for delay were as follows: 70% did not know how serious the pathology was; 56% thought that it had spontaneous cure; 16% did not have money to pay for ophthalmic evaluation, 10% did not know where to go and 24% for other reasons. Conclusion . Educational programs about disease and measures to optimize the referral to specialized services are needed to accelerate the treatment of patients with rhegmatogenous retinal detachment.